Effects of copper in sediments on benthic macroinvertebrate communities in tropical reservoirs - Beghelli, F. G.S. [UNESP]; Pompêo, M. L.M.; Rosa, A. H. [UNESP]; Moschini-Carlos, V. [UNESP] (My University, 2016)
Copper (Cu) is an essential trace element but can be toxic to biota when present above a certain threshold concentration. There are many anthropogenic sources of copper, which can accumulate in sediments. Benthic macroinvertebrates (BMI) are organisms that inhabit the sediments, so they can be good indicators of sediment toxicity. The objective of this work was to test BMI community responses to a range of Cu concentrations in sediments. For this purpose, we used mouthpart alterations and bioaccumulation as endpoints. Sediment sampleswere collected, and in situ analyses of water variables were conducted at nine sampling points distributed along three interconnected reservoirs of the Cantareira System in Sao Paulo State, Brazil. Copper concentrations were determined in the sediments, chironomid larvae and oligochaetes. The results indicated that contamination of the sediments collected from the Paiva Castro reservoir was sufficient to cause Cu bioaccumulation in larval Chironomidae. No bioaccumulation was observed in oligochaetes or in any of the organisms from control locations. A linear model, rather than the logistic model generally considered in dose-response assays, best fitted the observed mouthpart alterations and Cu concentrations. Extrapolation of the model indicated that a Cu concentration of 58.60 mg/Kg, instead of the proposed PEL value of 108 mg/Kg, would be sufficient to cause observable alterations in 50% of the Chironomidae larvae. Moreover, our results showed that Cu levels higher than 13 mg/Kg can cause adverse effects in BMI communities and that the levels found in the Paiva Castro reservoir (15.19-41.18 mg/Kg) were sufficient for bioaccumulation in chironomids.
Keywords: Chironomidae; Ecotoxicology; macroinvertebrate community; tropical reservoirs.